Practical use of idarucizumab - G. R. Ramazanov; E. A. Kovaleva; E. V. Klychnikova; S. S. Petrikov; N. A. Shamalov; I. S. Aliev; E. V. Shevchenko (Кардиоваскулярная терапия и профилактика, 2023)
The number of patients with indications for direct oral anticoagulants (DOACs) to prevent thrombotic events is steadily growing. However, in 1,1-2,2% of cases, ischemic strokes occur within DOAC therapy. In this case, DOAC use is a limitation for systemic thrombolysis, except for available reversal of anticoagulation. In order to immediately inactivate the anticoagulant effect of dabigatran etexilate (DE), reversal agent idarucizumab is used.Aim. To evaluate the effectiveness and safety of idarucizumab in clinical practice.Material and methods. The study included 9 patients taking DE who developed urgent conditions that required emergency reversal of anticoagulation with idarucizumab.Results. Normalization of thrombin time (TT) was achieved in 7 (77,8%) patients immediately after idarucizumab administration. In two patients, 10 minutes after the administration of a specific DE reversal agent, TT decreased, but did not reach reference values (case 1: TT decreased from 181 to 23,3 seconds; case 2: TT decreased from 181 to 18,3 seconds); 30 minutes after the idarucizumab administration, TT normalization was achieved.Conclusion. Nobody developed clinically significant arterial and/or venous thrombotic events during the entire period of hospitalization. Rapid reversal of anticoagulation with idarucizumab allows immediate systemic thrombolytic therapy or surgery in patients taking DE without the increase of bleeding or thrombosis risk and the need for control coagulation analysis.